2007
DOI: 10.1160/me0387
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Sampling Strategies on Score Results of the Nine Equivalents of Nursing Manpower Use Score (NEMS)

Abstract: Summary Objective: Prospective observational study to assess the impact of two differentsampling strategies on the score results of the NEMS, used widely to estimate the amount of nursing workload in an ICU. Methods: NEMS scores of all patients admitted to the surgical ICU over a one-year period were automatically calculated twice a day with a patient data management system for each patient day on ICU using two differentsampling strategies (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
6
0
3
Order By: Relevance
“…O Nine Equivalents of Nursing Manpower Use Score tem sido utilizado em diversos estudos para avaliar gestão de recursos humanos em UTI, avaliação e comparação de nível de trabalho em UTI, bem como para a previsão e o planejamento de pessoal de enfermagem individual e coletivamente (estudos multicêntrico) em UTI (11,12,17,18) . Desenvolver sistema de escore de intervenção terapêutica baseado no TISS-28 e validá-lo em base de dados independente 9 itens correspondentes a procedimentos e intervenções realizadas dentro ou fora da UTI.…”
Section: Nine Equivalents Of Nursing Use Manpowerunclassified
See 1 more Smart Citation
“…O Nine Equivalents of Nursing Manpower Use Score tem sido utilizado em diversos estudos para avaliar gestão de recursos humanos em UTI, avaliação e comparação de nível de trabalho em UTI, bem como para a previsão e o planejamento de pessoal de enfermagem individual e coletivamente (estudos multicêntrico) em UTI (11,12,17,18) . Desenvolver sistema de escore de intervenção terapêutica baseado no TISS-28 e validá-lo em base de dados independente 9 itens correspondentes a procedimentos e intervenções realizadas dentro ou fora da UTI.…”
Section: Nine Equivalents Of Nursing Use Manpowerunclassified
“…O TISS-28 foi traduzido e validado para o português através de um estudo (9) . Este escore otimizou o tempo de coleta de dados (10) , ainda que estudos apontem como limitação do escore o tempo despendido na realização desta rotina (11) .…”
Section: Introductionunclassified
“…In addition, studies conducted in several countries have sought to evaluate and/or relate NEMS scores for hospitalized patients to the mortality prognosis, as well as the quantification of nursing workload, seeking comparisons between different ICUs. The main advantages of using NEMS are the reduction in data collection time and the ease with which this score can be applied . Limitations were also observed in studies, where it was found that NEMS has less discriminative power when compared with TISS‐28: patients with the same score do not always require the same care; patient age can influence the score value; it does not include nursing activities not related to patient care …”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of using NEMS are the reduction in data collection time and the ease with which this score can be applied. [4][5][6] Limitations were also observed in studies, where it was found that NEMS has less discriminative power when compared with TISS-28: patients with the same score do not always require the same care; patient age can influence the score value; it does not include nursing activities not related to patient care. 7 Research with nursing indicators is still ongoing in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…(1,5,6) The NEMS is also appropriate for the management of nursing professionals who work in intensive therapy and for the evaluation of ICUs. (7)(8)(9) Studies validating NEMS were implemented with clinical and surgical patients hospitalized in adult ICUs, (4,10) however, such studies are rare and seldom implemented in pediatric units.…”
Section: Introductionmentioning
confidence: 99%